A survey of active quasi-circulators. (November 2020) - Tang, Bingjun; Geng, Li
Abstract: With the development of multi-band wireless communication and the increasing data transmission rate, the circulator as an antenna interface must be able to work in multiple frequency bands and provides large bandwidth. It presents a high challenge to the design of circulators, especially the active quasi-circulators. In this survey, we review the representative active quasi-circulators and summarize three different techniques and the corresponding structures to show an incremental improvement of the isolation and bandwidth of the active quasi-circulators. In addition, we also compare the performance of several state-of-art active circulators, and analyze their advantages and disadvantages. Finally, we conclude the future trend of the active quasi-circulators.